Effectiveness of Scalp Cooling in Preventing Chemotherapy induced Alopecia - J, Rasna; C V, Bijoy; B, Feba; K, Geetha; A, Vijayakumar (Indian Journal of Pharmacy Practice)
Chemotherapy induced alopecia is the most distressing feature in cancer treatment. The technique of continuous cooling of scalp during chemotherapy reduces the temperature of scalp and causes vasoconstriction of blood vessels thereby decreasing the amount of drug that reaches the blood. This study tested the effectiveness of scalp cooling using the Paxman scalp cooler system. It also attempted to measure simultaneously the relative effectiveness of anthracycline, antimetabolite and taxane group of drugs. Hair loss was assessed using WHO scale and OLSEN/Canfield visual aided scale (VAS). Extent of alopecia was analyzed before and after providing scalp cooling. The study clearly showed that scalp cooling with Paxman scalp cooler was effective in preventing chemotherapy induced hair loss. It was also found that the highest protection was obtained in the case of taxane group of drugs (93.3%), followed by antimetabolite (pemetrexed, gemcitabine) group of drugs (80%) and the least effective was anthracycline group of drugs (30%). Scalp cooling effectiveness was found out using an experimental group and control group consisting of thirty samples each and the study was found to be statistically significant (p˂0.001). Association between the three drug groups and scalp cooling efficacy was also found to be statistically significant (p˂0.05). Age, gender, number of cycles and sites of cancer did not have any significant association with scalp cooling effectiveness implying that irrespective of age, gender, number of cycles or site of cancer, scalp cooling can be used to prevent chemotherapy induced alopecia.
Keywords: Chemotherapy; Scalp cooling; alopecia; WHO scale; Olsen/canfield scale